FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGELAPAN PAJAK (Studi pada Wajib Pajak Orang Pribadi Yang Terdaftar di Kantor Pelayanan Pajak Pratama Tampan) - Lya Octavia; Desmiyawati Desmiyawati; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of the tax justice, tax rate, tax system, tax information and technology, precision possible fraud detected and government appropriation to tax evasion. The population in this study were all individuals who become individual taxpayers registered in the Primary Tax Office Tampan. types of samples used by researchers is convinience sampling. The samples in this study were the individual taxpayer whoever enjoyed the service at the Tax Office Primary Tampan Pekanbaru. The samples used in this study was 100 respondents. This hypothesis is then tested using multiple linear regression analysis with SPSS version 20. These results indicate that tax fairness, tax rates, the tax system, taxation and information technology and the possibility of fraud detected effect on tax evasion. While the accuracy of government does not affect the allocation of tax evasion. The magnitude of the effect of the independent variable on the dependent variable was 74.1%. While 25.9% are influenced by other variables not included in this regression model.Keyword: tax justice, tax rate, tax system, tax information and technology, precision possible fraud detected and government appropriation